2022
DOI: 10.1007/s13399-022-02837-y
|View full text |Cite
|
Sign up to set email alerts
|

Moesziomyces spp. cultivation using cheese whey: new yeast extract-free media, β-galactosidase biosynthesis and mannosylerythritol lipids production

Abstract: Mannosylerythritol lipids (MELs) are biosurfactants with excellent biochemical properties and a wide range of potential applications. However, high production costs, low productivity and unsatisfactory scale-up production have hampered commercial adoption. Herein, we report for the first time the β-galactosidase production by Moesziomyces spp. from different sugars (D-galactose, D-glucose and D-lactose), with D-galactose being the best β-galactosidase inducer, with 11.2 and 63.1 IU/mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Mannosylerythritol lipids (MELs) used in this study were produced by Moesziomyces antarcticus PYCC 5048 T (CBS 5955) and M. aphidis PYCC 5535 T , provided by the Portuguese Yeast Culture Collection (PYCC), CREM, FCT/UNL, Caparica, Portugal, following previously established fermentation medium and conditions [ 19 ]. Yeasts were cultivated in a 2-L bioreactor (New Brunswick TM Bioflo R /CelliGen R 115), using 1.5 L of working volume, with a medium composition described elsewhere [ 32 ]. The temperature was set up at 27 °C and the pH was not controlled.…”
Section: Methodsmentioning
confidence: 99%
“…Mannosylerythritol lipids (MELs) used in this study were produced by Moesziomyces antarcticus PYCC 5048 T (CBS 5955) and M. aphidis PYCC 5535 T , provided by the Portuguese Yeast Culture Collection (PYCC), CREM, FCT/UNL, Caparica, Portugal, following previously established fermentation medium and conditions [ 19 ]. Yeasts were cultivated in a 2-L bioreactor (New Brunswick TM Bioflo R /CelliGen R 115), using 1.5 L of working volume, with a medium composition described elsewhere [ 32 ]. The temperature was set up at 27 °C and the pH was not controlled.…”
Section: Methodsmentioning
confidence: 99%
“…A study by (Nascimento et al, 2023) methods can be challenging due to the interference of biomass with downstream separation processes-biomass will also be collected along with precipitated MELs. Consequently, additional cell separation techniques may be required before implementing an in situ precipitation process (Teke, Tai, et al, 2022).…”
Section: Membrane Filtrationmentioning
confidence: 99%
“…These studies led to a good understanding of the optimal conditions for labscale MEL production in shake flasks. It has been observed that vegetable oils, most notably soybean oil, serve as the optimal carbon F I G U R E 6 An illustration of the proposed downstream process which integrates solvent selective dissolution and organic solvent nanofiltration (OSN) for the purification of mannosylerythritol lipids modified from Nascimento et al (2023).…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-treated lignocellulosic residues by an enzymatic process were fed to M. antarcticus PYCC 5048 T and M. aphidis PYCC 5535 T to produce MEL [23]. Other hydrophilic sources have been recently assessed, such as the use of coconut water [24], cassava wastewater [25], or cheese whey [26]. While these studies using hydrophilic carbon sources report low accumulation of residual lipids, the titres obtained are still low.…”
Section: Introductionmentioning
confidence: 99%